Zfp57 Exerts Maternal and Sexually Dimorphic Effects on Genomic Imprinting - Xu, Zhen; Shi, Jiajia; Zhang, Yu; Liu, Yuhan; Zhao, Junzheng; Chen, Qian; Song, Chenglin; Geng, Shuhui; Xie, Wei; Wu, Feizhen; Bai, Yun; Yang, Yang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Zfp57 has both maternal and zygotic functions in mouse. It maintains genomic imprinting at most known imprinted regions and controls allelic expression of the target imprinted genes in mouse embryos. DNA methylation imprint at many imprinting control regions (ICRs) is lost when both maternal and zygotic Zfp57 are absent in Zfp57 maternal-zygotic mutant mouse embryos. Interestingly, we found that DNA methylation at a few ICRs was partially lost without maternal Zfp57 in the Zfp57 heterozygous mouse embryos derived from the Zfp57 homozygous female mice. This suggests that maternal Zfp57 is essential for the maintenance of DNA methylation at a small subset of imprinted regions in mouse embryos. This maternal effect of Zfp57 was applied to allelic expression switch as well as expression levels of the corresponding imprinted genes. It is rather surprising that DNA methylation imprint was affected differently at Rasgrf1 and AK008011 imprinted regions in the female or male Zfp57 maternal-zygotic mutant embryos, with more significant loss of DNA methylation observed in the male mutant embryos. Loss of ZFP57 resulted in gender-specific differences in allelic expression switch and expression level changes of some imprinted genes in the female or male mutant embryos. These results indicate maternal and sexually dimorphic effects of ZFP57 on genomic imprinting in mouse.